The earliest cut marks of Europe: a discussion on hominin subsistence patterns in the Orce sites (Baza basin, SE Spain) - Espigares-Ortiz, María Patrocinio; Palmqvist-Barrena, Carlos Paul; Guerra-Merchán, Antonio; Ros-Montoya, Sergio; García-Aguilar, José Manuel; Rodríguez-Gómez, Guillermo; Serrano-Lozano, Francisco; Martínez-Navarro, Bienvenido (Nature, 2019)
Ancient evidence of human presence in Europe is recorded in several Early Pleistocene archaeopalaeontological sites from Spain, France and Italy. This is the case of Barranco León (BL) and Fuente Nueva-3 (FN-3), two localities placed near the town of Orce (depression of Baza and Guadix, SE Spain) and dated to ~1.4 Ma. At these sites, huge assemblages of Oldowan tools and evidence of defleshing, butchering and marrow processing of large mammal bones have been recovered together with a deciduous tooth of Homo sp. in the case of level BL-D. In this study, we: (i) describe in detail the anthropic marks found in the bone assemblages from these sites; (ii) analyse patterns of defleshment, butchery and marrow processing, based on the modifications identified in the cortical surface of the fossils; and (iii) discuss on the subsistence strategies of the first hominins that inhabited the European subcontinent during Early Pleistocene times.
Keywords: Arqueología - Baeza; human; Early Pleistocene; Fuente Nueva 3; Barranco León; Cut Marks